Analisa Metode Monte Carlo Dalam Menentukan Rute Terpendek Pada Ojek Online - Rumputra Rumputra; Garuda Ginting; Saidi Ramadan Siregar (STMIK Budi Darma, 2020)
The development of Information Technology has a huge impact on various sides of life, from government, administration, economy, and education. Regarding the issue of education in particular, the use of information technology will bring very good changes in the education system in which the material presented will be developed. With the existence of computer technology as a support in processing data and information, it has become a necessity for all humans, so that the required information can be obtained quickly and accurately. In fact, one of the most important factors in information technology problems is the problem of network or media access which becomes a bridge between learning resources and parties involved in the learning process. The online motorcycle taxi simulation process using the Monte Carlo method is very good in developing the level of knowledge in the general public, so that the use of information technology can be of maximum benefit to every level of society.